PERKEMBANGAN JUMLAH UANG BEREDAR DI INDONESIA - B01110090, NINDYA LESTARI (Jurnal Curvanomic, 2014)
This study aims to determine the amount of income the proportion of people who are held in cash, comparison between currency, demand deposits, and quasy money as well as look at the amount of the value of M1 in West Kalimantan and determine the impact on the economy in West Kalimantan. In this study, the writer uses descriptive and qualitative. From the analysis result, the proportion of people’s income earned in cash held shows values of 1,26 and in accordance with theory from Alfred Marshall about the quantity of money. Comparison between currency, demand deposits, and quasy money in Indonesia shows that quasy money is the most dominant, which is consistent with the statement Keynes where people will hold money for speculative motives with objective large reward. Value of M1 in West Kalimantan is always increase, but the funds are channeled out West Kalimantan. Credit score is the biggest concumption credit so the impact is inflation is high. Therefore, the government and society should support each other in order to promote the improvement of infrastructure loans increased investment in West Kalimantan. Keyword : Money Supply (M2)